Immunotherapy: State-of-the-art review of therapies and theratypes - Agache, Ioana; Zemelka-Wiącek, Magdalena; Shamji, Mohamed H.; Jutel, Marek (Journal of allergy and clinical immunology, 2022)
Through its disease-modifying potential, immunotherapy is the keystone to curing allergic diseases. Allergen immunotherapy, applied for more than a century, is currently supported by novel modalities such as mAb-based therapies or small molecules targeting the key nodes of the allergic inflammation network. In this review, a summary of the most significant advances in immunotherapy is presented, addressing not only novel approaches to stratifying patients but also major controlled clinical trials and real-world evidence that strengthen the role of immunotherapy in the treatment of allergies.